Invasive pneumococcal disease in adults after the introduction of pneumococcal vaccination: a retrospective study in the metropolitan area of Zagreb, Croatia (2010–2022) - Čivljak, Rok; Draženović, Karla; Butić, Iva; Kljaković Gašpić Batinjan, Marina; Huljev, Eva; Vicković, Ninoslava; Lizatović, Ivan Krešimir; Grgić, Borna; Budimir, Ana; Janeš, Andrea; Nikić Hecer, Ana; Filipec Kanižaj, Tajana; et al. (Frontiers in Public Health, 2024)
IntroductionInvasive pneumococcal disease (IPD) is a severe form of illness caused by Streptococcus pneumoniae with high morbidity and mortality rate in the general population, particularly in children <5 years of age, adults ≥65 years of age and the immunocompromised. As known, pneumococcal vaccination lowers the risk of IPD so the aim of this study was to investigate whether the introduction of pneumococcal vaccination has influenced the incidence and mortality of IPD in adults in Croatia.Materials and methodsA retrospective study was conducted among adult patients (aged ≥18 years) hospitalized due to IPD in the metropolitan area of Zagreb from 1st January 2010 to 31st December 2022. Number of vaccine doses distributed were obtained from the healthcare system.ResultsDuring the study period, 389 patients were hospitalized, of whom 214 (55.5%) were male. The annual incidence of IPD ranged from 0.6 to 4.1/100,000 population. A total of 185 (47.6%) patients were ≥ 65 years of age and 309 (79.4%) were ≥ 50 years of age. In 331 (85.1%) of the patients, at least one risk factor was identified, with age ≥ 65 years being the most common. Bacteremic pneumonia was the most frequent clinical presentation of IPD (66.3%). Indication for vaccination had 249 patients (64%) but only 11 patients (4.4%) were vaccinated. Also, 64 patients (16.5%) died. Serotype was determined in 233 (59.9%) of the isolates, with serotype 3 being the most frequent (49, 21%), followed by serotype 14 (38, 16.3%) and 19A (15, 6.4%). A total of 180 isolates (77.3%) were included in the 13-valent conjugate vaccine, 208 (89.3%) in the 20-valent conjugate vaccine and 212 (91%) in the 23-valent pneumococcal polysaccharide vaccine.DiscussionThe introduction of pneumococcal vaccination has led to a significant decrease in the incidence and mortality of IPD in adults. To further reduce morbidity and mortality from IPD, it is necessary to increase vaccine coverage in adults, particularly in individuals with risk factors. It may be beneficial to lower the recommended vaccination age from ≥65 to ≥50 years as the substantial difference in the incidence rates of IPD between these age groups was noticed.